Transfer of preclinical study data on the influence of cimicifuga racemosaon functional changes in the hippocampus during menopause - Petra Stute; Hans-Heinrich Hen; Petra Nicken (Taylor & Francis Group, 2024)
Menopausal transition in women involves complex neurobiochemical changes linked to ovarian dysfunction, resulting in symptoms like vasomotor symptoms (VMS), sleep disturbances, anxiety, and cognitive impairments. Hormone replacement therapy is the first-line treatment. However, many women are reluctant to use HRT or have contraindications toward HRT and seek for alternatives. Non-hormonal therapies with extracts of Cimicifuga racemosa rhizomes like the isopropanolic extract (iCR, black cohosh) offer a promising alternative. A preclinical pilot study exploring iCR's effects on gene expression in the hippocampus and hypothalamus of ovarectomized (OVX) rats mimicking menopausal conditions identified important signaling pathways and CNS-based contributions to the multitargeted modes of action of iCR. Especially in the hippocampus, iCR compensated effects of OVX on gene expression profiles. These changes are reflected by the genes AVPR1A, GAL, CALCA, HCRT, PNOC, ESR1, ESR2 and TAC3 contributing to the formation of hot flushes or thermoregulation as well as to secondary effects such as blood pressure, metabolism, hormonal regulation, homeostasis, mood regulation, neuroendocrine modulation, regulation of sleep and arousal, and in learning, memory and cognition. To understand the mechanisms in the brain of estrogen-depressed animals (OVX) and subsequent iCR treatment we combined the results of the pilot study with those of up-to-date literature and tried to transfer the current knowledge to humans during menopausal transition and adaptation. Focus was laid on changes in the hippocampal function, that is disturbed by hormonal fluctuations, but can also be brought back into balance by iCR.